The Effect of Study Abroad on Grammatical Accuracy of Indonesian Students’ Oral and Written Performance - Kristian Adi Putra (PAROLE: Journal of Linguistics and Education, 2013)
This  correlational  study investigates the  effect  of  study  abroad  of two  exchange  students (SA) from  Indonesia  in  public  schools  in the United  States  on  their  grammatical  accuracy as  compared  to the oral and written performance of two first year college students through  formal  instruction (FI) in  Indonesia  never  experiencing living  in  L2  environment.  Speech  samples  were  elicited  through interview via-Skype, while writing samples were obtained through writing task. The result of this study shows that in oral and written performance, SA participants used more accurate grammar than FI participants.  However,  SA  participants  were  more  accurate  in using  the  three  tenses  in  writing (90%) than  in  speaking  (87%), while FI participants showed different result, i.e. their grammatical accuracy of speaking (78%) was higher than that of writing (76%).Studi  korelasional  ini  meneliti  efek  studi  di  luar negeri  untuk dua siswa  Indonesia  program  pertukaran (SA) di  sekolah  negeri Amerika Serikat  dalam  hal  ketepatan  gramatikal  yang dibandingkan dengan ketrampilan lesan dan tulis mahasiswa tahun pertama  melalui  instruksi  formal  (FI) di  Indonesia  yang  belum pernah  tinggal  di  lingkungan  bahasa  kedua. Sampel  ketrampilan lesan dikumpulkan lewat wawancara via Skype, sedangkan sampel ketrampilan tulis  diperoleh  melalui  tugas  mengarang.  Hasil penelitian  ini  menunjukkan  bahwa dalam  ketrampilan lesan  dan tulis,  akurasi  gramatikal  peserta  SA  lebih  tinggi  daripada  peserta FI. Namun demikian, peserta SA lebih akurat dalam menggunakan tiga kala dalam mengarang (90%) daripada penggunaan kala dalam berbicara  (87%),  sementara  peserta  FI menunjukkan  hasil  yang berbeda,  yaitu  akurasi  gramatikal  berbicara  (78%)  lebih  tinggi daripada akurasi gramatikal mengarang (76%).